Pathophysiology of GvHD and Other HSCT-Related Major Complications - Ghimire, Sakhila; Weber, Daniela; Mavin, Emily; Wang, Xiao nong; Dickinson, Anne Mary; Holler, Ernst (Frontiers in Immunology, 2017)
For over 60 years, hematopoietic stem cell transplantation has been the major curative therapy for several hematological and genetic disorders, but its efficacy is limited by the secondary disease called graft versus host disease (GvHD). Huge advances have been made in successful transplantation in order to improve patient quality of life, and yet, complete success is hard to achieve. This review assimilates recent updates on pathophysiology of GvHD, prophylaxis and treatment of GvHD-related complications, and advances in the potential treatment of GvHD.